The Use of Touch in Counseling: An Ethical Decision‐Making Model. Issue 1 (4th April 2013) - Calmes, Stephanie A.; Piazza, Nick J.; Laux, John M.
<x xml:space="preserve">Abstract</x> Although some counselors have advocated for the limited use of touch in counseling, others have argued that touch has no place within the counseling relationship. Despite the controversy, the use of touch has been shown to have a number of therapeutic benefits; however, there are few ethical decision‐making models that are appropriate for considering the use of touch in counseling. The authors discuss the controversy surrounding the use of touch and the benefits/contraindications of touch. The 5 ethical principles of counseling are also examined; a new ordering of the principles is presented as a useful ethical decision‐making model when considering the use of touch in counseling.